(untitled) (Revista Latino-Americana de Enfermagem, 2005)
This study presents a survey conducted among 132 Tuberculosis patients submitted to Supervised Treatment between 01/1998 and 12/1999, with a view to describing epidemiological aspects, according to the gender, (final) treatment result and HIV immunology result variables. The number of patients covered by Supervised Treatment rose from 19% to 30%. For each of these years, 64% and 71% of the patients were male, while 89% and 77% evolved towards cure. The rate of abandonment increased from 7% to 10%, while 4% and 10% of the patients died of Tuberculosis. The Tb/HIV co-infection represented 22% and 42% of the cases. The obtained results disclosed a tendency towards the gradual amplification of Supervised Treatment and its implementation implied.